Healthcare Access Barriers, Socioeconomic, and Perceived Dental Needs Associated with Dental Self-Treatment Among Non-Utilizing Adults - Fadli Alwi; Eka Julianti; Lia Handayani (Cakradonya Dental Journal, 2026)
Dental self-treatment represent a significant public health challenge in Indonesia, accompanied by persistently low utilization of professional dental services. This study investigated the association between barriers to healthcare access and dental self-treatment among adults in Aceh, Indonesia, while adjusting for socioeconomic factors and perceived dental health needs. This cross-sectional study analysed data from N=11,061 non-users of dental services with reported dental and oral health needs (aged ≥25 years) derived from the 2023 Indonesian National Health Survey (SKI). Multilevel Poisson regression was applied to estimate prevalence ratios (PRs) with 95% confidence intervals (CIs). The results show prevalence of dental self-treatment was 47.7%, with significant district-level variation (VPC=3.83%). After adjusting for covariates, prolonged waiting time (PR=1.48; 95% CI: 1.35–1.63) and financial constraints (PR=1.20; 95% CI: 1.05–1.37) were associated with self-treatment. A cumulative effects following a dose-response pattern: individuals experiencing only one healthcare access barrier  had a higher prevalence of self-treatment (PR=1.43; 95% CI: 1.27–1.60), while those facing three barriers (waiting time, financial constraints, and distance) showed an even stronger association (PR=2.01; 95% CI: 1.63–2.47). These findings may reflect a systemic access limitations. The higher prevalence of dental self-treatment may be explained by the coexistence of clinical urgency, structural barriers, and socioeconomic vulnerabilities.